A one pass parallel hexagonal thinning algorithm - Staunton, R.C (7th International Conference on Image Processing and its Applications, 1999)
The development of a fully parallel hexagonal thinning algorithm is reported and compared with a similar algorithm for use with rectangularly sampled images. Both algorithms produced good skeletons, but the hexagonal could be implemented with only 50% of the logical operations required by the rectangular.